2020
DOI: 10.1029/2020wr027629
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Ratios With Age: Application to Preasymptotic One‐Dimensional Equilibrium Bimolecular Reactive Transport in Porous Media

Abstract: Analysis of reactive transport in natural and engineered porous media has benefited from the concept of mixing ratios, in particular as a basis for mathematical separation of transport and reactions processes. General use of solute age has also been recently explored as a way to describe solute mass transfer and/or as a proxy for reaction extent. Age here is defined as exposure time to the flow field. Pairing these concepts, we develop mixing ratio models that are structured on age. One‐dimensional transport i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 61 publications
(198 reference statements)
1
16
0
Order By: Relevance
“…Yet, the observed degree of incomplete reaction is ostensibly larger than in our results. Multiple factors (or a combination of them) could explain this discrepancy, including the subtle differences in initial and boundary conditions at the interface (Gurung and Ginn, 2020), the possible influence of the lateral walls of the column on the flow and transport in G02, or the irregular geometry of the grains (as opposed to the spherical grains employed here). Below we explore the possible influence on the results of yet another element.…”
Section: Impact Of Local Concentration Variability On Measurementsmentioning
confidence: 95%
See 1 more Smart Citation
“…Yet, the observed degree of incomplete reaction is ostensibly larger than in our results. Multiple factors (or a combination of them) could explain this discrepancy, including the subtle differences in initial and boundary conditions at the interface (Gurung and Ginn, 2020), the possible influence of the lateral walls of the column on the flow and transport in G02, or the irregular geometry of the grains (as opposed to the spherical grains employed here). Below we explore the possible influence on the results of yet another element.…”
Section: Impact Of Local Concentration Variability On Measurementsmentioning
confidence: 95%
“…Recognizing the importance of the mixing process and the need for upscaled reactive transport models that implicitly account for it, numerous modeling approaches have been proposed in recent years to model mixing-limited reactive transport from a variety of perspectives (e.g., Oates, 2007;Benson and Meerschaert, 2008;Edery et al, 2009;Sanchez-Vila et al, 2010;Ding et al, 2013;Chiogna and Bellin, 2013;Hochstetler and Kitanidis, 2013;Paster et al, 2013Paster et al, , 2014Porta et al, 2016;Schmidt et al, 2017Schmidt et al, , 2018Schmidt et al, , 2019Ginn, 2018;Sole-Mari et al, 2020;Gurung and Ginn, 2020). In order to validate these new formulations, most authors test their models against laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Formulation of an accurate macroscale representation of the complex nonlinear reactions that occur at the microscale is one of the biggest challenges facing field-scale mechanistic modeling [ 124 , 137 , 157 ]. Currently, no one macroscale approach has been found that can produce reliable simulations of complex nonlinear geochemical fate and transport in all porous medium systems of interest [ 124 , 136 , 137 , 156 , 157 ]. What has been well established is that macroscale models do not follow a similar form to their microscale counterparts, and assuming so can introduce large errors [ 135 137 , 157 , 177 ].…”
Section: Mechanistic Modelingmentioning
confidence: 99%
“…What has been well established is that macroscale models do not follow a similar form to their microscale counterparts, and assuming so can introduce large errors [ 135 137 , 157 , 177 ]. Mathematically, the issue arises when attempting to represent averages of nonlinear microscale quantities as a non-linear combination of macroscale averaged quantities that is of the same functional form as the microscale form [ 114 , 135 , 136 , 177 ]. Put another way, assuming that each region of a macroscale model can be modeled as a batch system with known inputs and outputs introduces significant errors.…”
Section: Mechanistic Modelingmentioning
confidence: 99%
See 1 more Smart Citation